The TREAT‐NMD DMD Global Database: Analysis of More than 7, 000 Duchenne Muscular Dystrophy Mutations. Issue 4 (17th March 2015) - Bladen, Catherine L.; Salgado, David; Monges, Soledad; Foncuberta, Maria E.; Kekou, Kyriaki; Kosma, Konstantina; Dawkins, Hugh; Lamont, Leanne; Roy, Anna J.; Chamova, Teodora; Guergueltcheva, Velina; Chan, Sophelia; et al.
<x xml:space="preserve">Abstract</x> Analysing the type and frequency of patient specific mutations giving rise to Duchenne Muscular Dystrophy (DMD) is an invaluable tool for diagnostics, basic scientific research, trial planning and improved clinical care. We describe the development and analysis of the TREAT‐NMD DMD Global database (http://umd.be/TREAT_DMD/). We analysed and reported genetic data for 7149 DMD mutations held within the database. Additionally, we identified mutations within the database that would potentially benefit from novel genetic therapies for DMD including stop codon read‐through therapies. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>